Effects of chlorine dioxide on morphology and ultrastructure of Fusarium sulphureum and its virulence to potato tubers - Mei, Li; Shilong, Tian; Jin, Shen; Xizhuo, Wang; Jianxin, Cheng; Shouqiang, Li; Xia, Ge; Jiachun, Tian (International Journal of Agricultural and Biological Engineering, 2017)
The inhibitory effect and its virulence of chlorine dioxide (ClO2) against dry rot of potato were investigated. Potatoes were treated by ClO2, then observed for indoor bioassay, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to observe the morphology and ultrastructure of hyphae, and evaluated the control efficiency of ClO2 on potato tuber (LK99) dry rot by F. sulphureum pre-treatment. The results showed that the pathogen of potato dry rot was sensitive to ClO2, the virulence of regression of y = 5.05 + 7.308x, EC50 and EC90 were 0.3490 and 0.6261 respectively, the treatment of ClO2 could significantly inhibit the spore germination and mycelium growth of F. sulphureum, which was in a concentration-dependent manner, SEM and TEM observed that the morphology and ultrastructure of F. sulphureum hyphae were regularly damaged by ClO2, in vivo experiment further indicated that ClO2 could effectively control the dry rot of potato tubers with F. sulphureum, and ClO2 at the concentration of 0.75 ug/mL could significantly reduce the incidence of potato tuber dry rot and lesion expansion rate. The study showed that ClO2 could greatly against the pathogen of F. sulphureum, which could provide a scientific theoretical basis for the safe and efficient application of ClO2 in the prevention and control of potato diseases after harvest.Keywords: potato, dry rot, chlorine dioxide, Fusarium sulphureum, virulence, morphology and ultrastructureDOI: 10.25165/j.ijabe.20171005.2403Citation: Li M, Tian S L, Shen J, Wang X Z, Cheng J X, Li S Q, et al. Effects of chlorine dioxide on morphology and ultrastructure of Fusarium sulphureum and its virulence to potato tubers. Int J Agric & Biol Eng, 2017; 10(5): 242–250.